Changes in aquatic toxicity of potassium dichromate as a function of water quality parameters. (March 2017) - Kikuchi, Mikio; Syudo, Ayaka; Hukumori, Makoto; Naito, Chihiro; Sawai, Jun
Abstract: Potassium dichromate (K2 Cr2 O7 ) is used as a general reference toxicant in aquatic toxicity testing, but relatively little is known regarding the effects of water quality parameters on K2 Cr2 O7 toxicity to Daphnia magna . The acute toxicity of K2 Cr2 O7 to D. magna was comparatively examined in one very hard (M4 medium for D. magna assay), four hard, one moderately hard and one soft dilution water samples. The 48-h EC50 (50% effective concentration) of K2 Cr2 O7 to D. magna was reproducible (coefficient of variation [CV]: 13%) in tests using the same dilution water sample, but reproducibility was poor (CV: 62%) in tests using seven different dilution water samples. The observed 48-h EC50 value increased with increasing water hardness (28–250 mg CaCO3 /L) and Na + concentration (4.3–19.7 mg Na/L). The effect of Ca 2+ and Mg 2+ on K2 Cr2 O7 toxicity was equivalent in terms of molar concentration. The 48-h EC50 for K2 Cr2 O7 was determined according to OECD TG 202 by six contract laboratories using M4 medium and were shown to be reproducible (CV: 15%), indicating that the toxicity level can be determined with high accuracy if holding and dilution water samples are standardized. Multiple regression analysis revealed that the 48-h EC50 was strongly correlated ( r 2  = 0.927) with the Ca 2+, Mg 2+, Na + concentration, and alkalinity of the dilution water samples. Detailed monitoring of water quality characteristics thus facilitates intra- and inter-laboratory comparisons of toxicity data and enables predictions of changes in the susceptibility of test animals. Highlights: The 48-h EC50 was not reproducible under different dilution water samples. The interlaboratory 48-h EC50 in M4 medium was highly reproducible. The toxicity was affected by Ca, Mg and Na concentration of dilution water sample. A water quality–acute toxicity relationship equation was proposed. Prediction of changes in susceptibility of test animals should be facilitated.